The global course of the information revolution : recurring themes and regional variations - Hundley, Richard O. (Santa Monica, CA : National Defense Research Institute, Rand, 2003)
Advances in information technology are heavily influencing ways in which business, society, and government work and function around the globe, bringing many changes in a process commonly termed the "information revolution." Document portrays the state of the information revolution today--in its technological, business and financial, governmental, and social and cultural dimensions--and how it will likely progress in the next 10 to 15 years. Focuses separately on different regions of the world, including North America, Europe, the Asia-Pacific region, Latin America, the Middle East and North Africa, and Sub-Saharan Africa. Also looks in depth at recurring themes in information technology's impact around the world, including, for example, its influence on business models and its interrelationship with social and cultural value systems
Preface -- Figures -- Tables -- Summary -- Acknowledgments -- Abbreviations -- Introduction -- Part I, Recurring themes -- New technology developments will continually drive the information revolution -- The information revolution is enabling new business models that are transforming the business and financial worlds -- The information revolution is affecting mechanisms of governance and empowering new political actors -- The information revolution both shapes and is shaped by social and cultural values in significant ways -- Many factors shape and characterize a nation's approach to the information revolution -- Part II, Regional variations -- North America will continue in the vanguard of the information revolution -- The information revolution is following a somewhat different and more deliberate course in Europe -- Many Asia-Pacific nations are poised to do well in the information revolution, some are not -- Latin America faces many obstacles in responding to the information revolution: some nations will rise to the challenge, others will not -- Few Middle Eastern and North African nations will fully experience the information revolution, some may miss it altogether -- Most countries of Sub-Saharan Africa will fall further behind in the information revolution -- Part III, Some additional topics (A brief look) -- Geopolitical trends furthered by the information revolution could pose continuing challenges to the United States -- What future events could change these projections? -- The information revolution is part of a broader technology revolution with even profounder consequences -- Appendix: Participants in the Rand/NIC information revolution conferences -- References.
"MR-1680-NIC"--Page 4 of cover
"Prepared for the National Intelligence Research Council."
Includes bibliographical references (pages 163-174).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
Keywords: Information superhighway; Information technology; Digital communications; Information society; Electronic data processing; Autoroutes électroniques.; Technologie de l'information.; Transmission numérique.; Société de l'information.; information technology; COMPUTERS -- Web -- General; COMPUTERS -- Networking -- Intranets & Extranets; POLITICAL SCIENCE -- International Relations -- General; Electronic data processing; Digital communications; Information society; Information superhighway; Information technology; Electronic book